Investigation of antimicrobial effect of nerium oleander distillate - Burak Dik; Zafer Sayın; Orhan Çorum; Orhan (Eurasian Journal of Veterinary Sciences)
Aim: The aim of the current study was to determine the antimicrobial effect of Nerium oleander distillate. Material and Method: Collected Nerium oleander plant was identified and authenticated. Nerium oleander was washed and chopped, later sufficient distilled water was added. The mixture was distillated by distillatory device. After the plantdistillated water mixture was started to evaporate, vapor was separated to other clean glass containers. Obtained Nerium oleander distillate was lyophilized in small glass bottle, and dry material was collected. Lyophilized dry material was dissolved at concentration of 5 mg/mL with distillated water, and its antimicrobial effect was investigated against to Escherichia coli, Salmonella Typhimurium, Salmonella Enteritidis, Staphylococcus aureus, Methicillin Resistant Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pneumonia, Listeria monocytogenes, Pseudomonas aeruginosa and Candida ssp. by agar well-diffusion method. Result: Nerium oleander distillate did no show any antimicrobial effect against to tested microorganism. Conclusion: It may be stated that Nerium oleander distillate has no antimicrobial effect contrary to its chemical extracts.